Sensitivity and specificity of the Vectraplex electrocardiogram system with a cardiac electric biomarker in the diagnosis of ST-elevation myocardial infarction. Issue 3 (3rd July 2019) - Mixon, Timothy A.; Hardegree, Evan; Shah, Jinesh; Grable, Margarite; Fikes, Wanda
Abstract: ST-elevation myocardial infarction (STEMI) is a clinical diagnosis based on a compatible history and characteristic electrocardiographic changes. In the current era, STEMI is treated emergently with angiography, leading to percutaneous coronary intervention. However, false-positive electrocardiograms (ECGs) occur, resulting in unnecessary emergent catheterizations. We hypothesized that the Vectraplex cardiac electrical biomarker (CEB) would increase the specificity for the diagnosis of STEMI. We studied 50 patients who were identified by standard of care (clinical history, physical exam, and 12-lead ECG) as suspected to have STEMI and tested the sensitivity and specificity of the Vectraplex ECG system. Using the final clinical diagnosis (based on history, ECGs, troponin values, and angiographic findings) as the gold standard, we found the CEB value to be quite dynamic, with a reasonable sensitivity and a good positive predictive value but generally poor specificity and negative predictive value. It offered only a 20% improvement compared to 50-50 performance on receiver operator curves.